Comparison of 0.1% Bromfenac Sodium and 0.1% Pemirolast Potassium for the Treatment of Allergic Conjunctivitis - Miyake-Kashima, Minori; Takano, Yoji; Tanaka, Mari; Satake, Yoshiyuki; Kawakita, Tetsuya; Dogru, Murat; Asano-Kato, Naoko; Fukagawa, Kazumi; Fujishima, Hiroshi (Japanese journal of ophthalmology, 2004)
We compared the efficacy of a new nonsteroidal antiinflammatory drug (NSAID) eye drop, 0.1% bromfenac sodium (Bromfenac), with that of an antiallergic agent, 0.1% pemirolast potassium (Pemirolast), in the treatment of seasonal allergic conjunctivitis in Japanese patients. Twenty-two subjects with seasonal allergic conjunctivitis were enrolled in the study. One eye was treated with Bromfenac eye drops and the contralateral eye was treated with Pemirolast eye drops for 1 week. Subjective ocular symptoms and objective ocular signs evaluated by slit-lamp examination were scored and recorded before and after treatment. Both drugs significantly decreased ocular signs after 1 week, but not symptoms. No significant differences in subjective symptoms or objective signs were observed between the two drugs. Ten patients (45.5%) selected Bromfenac as more effective, nine patients (40.9%) selected Pemirolast, and three patients found no difference in efficacy between the two drugs. Bromfenac sodium is as safe and effective for the treatment of allergic conjunctivitis as pemirolast potassium.